O papel dos polissacarídeos algais extracelulares na dinâmica de metais no reservatório de Barra Bonita - Gouvêa, Sandra Protter (2004)
The influence of phytoplankton and their excreted materials in natural waters have been considered important issues among metal speciation studies. This work focused on the potential influence of the high molecular weight materials excreted by dominant phytoplankton species of Barra Bonita reservoir (Anabaena spiroides, Microcystis aeruginosa and Aulacoseira granulata) in the speciation and complexation of Cu and Cd. Therefore, this study comprised field and laboratory studies. Seasonal samplings were made during a period of two years in the reservoir. The total, ionic and organic concentrations of Cu and Cd were determined, as well as the complexation parameters with ligands present in the reservoir water. Also, the dissolved organic carbon and physico-chemical parameters of the water column were obtained. A speciation model was applied to metal complexation parameters and total metal concentrations obtained in field investigations. Laboratory cultures of the selected microalgae were made to obtain high molecular weight excreted materials. In a similar manner, the high molecular weight materials were isolated from the reservoir water. These materials were analysed for metal complexation with Cu and Cd, monosaccharide composition and elemental analysis (C, H, N and S). In the reservoir water, Cd speciation was dominated by ionic species, while Cu was mostly associated to the dissolved organic matter. Seasonal samplings presented Cu ligands with similar complexation parameters for the entire period studied. Cd complexation was not detected in the reservoir water. The speciation model resulted in similar Cu2+ concentration to the mean value obtained in field analyses, and indicated higher Cu association to the ligands of the reservoir water. Cu was complexed by all high molecular weight materials studied, while Cd was complexed solely by the cyanophyte materials. Higher proportions of acid monosaccharides in the high molecular weight materials corresponded to higher Cu and Cd complexation parameters, whereas no relation between C, H, N and S proportions and metal complexation properties of the high molecular weight materials was observed. The excreted materials of dominant microalgae from Barra Bonita reservoir had Cu ligands with intermediate to weak binding strength, as those present in the reservoir water. These results indicate the potential influence of such organic materials in metal speciation, bioavailability and mobility of metals with similar behaviour to that of Cu in the reservoir water.